STUDENTS' INTEREST IN ENGLISH ONLINE LEARNING PRACTICE AT XI TKJ 1 SMKN 1 GIRITONTRO IN THE ACADEMIC YEAR 2020-2021 - Sally Naritama; Agung Budi Kurniawan; Samsul Hadi (English Education Study Program STKIP PGRI Pacitan, 2022)
This study aims to find out students' Interest in English Online Learning reviewed from Aspects ofInterest, Elements of Interest, and Indicators of Interest. This research wasa case study. The approachused in this research was a qualitative descriptive research approach. Participants of this study weregrade XI students of TKJ,1 consisting of 36 students and 1 English teacher at SMKN 1 Giritontro.The data of this research were obtained from observations, documentation, and interviews. Dataanalysis techniques used qualitative analysis, namely data collection, data reduction, presentation,conclusion drawing, and verification. The results of the data analysis showed that the results ofobservations made by researchers on online learning videos in grade XI TKJ 1, namely onAspect ofInterest, with an average percentage of 46%, had a range of values with a description of LessInterest. While Element of Interest got, an average percentage result of 53% had a range of valueswith a description of Interest. Lastly, the Indicator of Student Interest got a result of 51%. Apercentage of 51% had a range of values with a descriptionof Interest.